Syntax in elementary school writing - Lozada Trimbath, Minnie Eloisa (2012)
The study explores aspects of the syntactic development of the written mother tongue of sixth grade primary students in national schools in Lima. This paper focuses on the occurrence of subordinate constructions in narrative texts produced by the students. Even though there is not yet a control of punctuation to separate sentences, it is possible to identify types of subordinating constructions. Among the most frequent, it is possible to see adverbial ones, especially those dealing with cause and time. The next more frequent are those that function as direct object. Concerning the control of the linguistic constructions mentioned before, one can observe that the majority of students that produce them handle them in an acceptable way. Nevertheless, one can notice the presence of certain types of mistakes, information that can also contribute to the planning of the teacher’s work. One can then say that, in the students handling of the language, there is a movement towards flexibility when dealing with syntax.